(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The current era is characterized by a digital revolution, and businesses and industries are undergoing accelerated transformation. Now, terms like "Industry 4.0," "digitalization," and "smart" are frequently employed to describe these adjustments. To thrive in the current era, even Livestock Farms must adapt to this transition and employ digitalization. However, Livestock Farmers may delay associating their industry with digitalization and AI. To aid them in this transition, a scientific study was conducted to determine which livestock processes are useful for digitalization and their industry-wide advantages. In addition, it examines the viability of emerging technologies such as blockchain, IoT, Big Data, and AI in animal husbandry. By understanding each process and its digital solution, the various periods of digitalization can be defined.